2009
DOI: 10.1097/gim.0b013e3181a53562
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic aspects of primary ciliary dyskinesia/Kartagener syndrome

Abstract: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous disorder of motile cilia. Most of the disease-causing mutations identified to date involve the heavy (DNAH5) or intermediate (DNAI1) chain dynein genes in ciliary outer dynein arms, although a few mutations have been noted in other genes. Clinical molecular genetic testing for PCD is available for the most common mutations. The respiratory manifestations of PCD (chronic bronchitis leading to bronchiectasis, chronic rhino-sinusitis and chronic otit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
375
0
23

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(406 citation statements)
references
References 177 publications
(235 reference statements)
8
375
0
23
Order By: Relevance
“…10,11 The axoneme structure of nasal mucosa of the patient is seen normal in the electron microscopy. Saccharin clearance time is normally 7 to 15 minutes.…”
Section: Discussionmentioning
confidence: 90%
“…10,11 The axoneme structure of nasal mucosa of the patient is seen normal in the electron microscopy. Saccharin clearance time is normally 7 to 15 minutes.…”
Section: Discussionmentioning
confidence: 90%
“…So; the ciliated epithelium situated in the airways, brain ventricles, oviducts, and vasa efferentia of the testes all may be affected. The classic syndrome is a triad of situs inversus, bronchiectasis, and sinusitis which was first described by Kartagener 1904 (Leigh et al 2009 Parmley et al 1958; found that the most commonly encountered cardiac lesion at necropsy was myocardial rupture of a septum or a chamber wall. Bjørnstad et al 2009 described a case with coronary artery dissection and acute myocardial infarction following blunt chest trauma.…”
Section: Situs Inversus Eg Kartagener Syndromementioning
confidence: 99%
“…The recently published European Respiratory Society (ERS) guidelines for the diagnosis of PCD provide recommendations on patient referrals [30]. Simple and easy-to-use predictive tools that provide disease probability scores, such as PICADAR (PrImary CiliARy DyskinesiA Rule) [3], and expert-defined clinical symptoms scores [10] will probably improve referrals from secondary care but require validation in different settings [26].…”
Section: Introductionmentioning
confidence: 99%